OPTIMIZATION OF POLY ALUMUNIUM CLORIDE (PAC) DOSAGE FOR TANNERY WASTE TREATMENT IN COAGULATION-FLOCULATION PROCESS - Nanda Brilian Tantri; Swatika Juhana; Ragil Yuliatmo (Politek ATK Yogyakarta Press, 2023)
The purpose of this study was to determine the optimum dose of PAC coagulant in the treatment of tannery waste in the coagulation-flocculation process. The research was conducted using the jar test method to treat leather tanning wastewater by coagulation-flocculation. Coagulation was carried out with various doses of PAC coagulant 1%, 2%, 3%, 4%, and 5% each of which 5 mL was put into a beaker containing 300 mL of tannery wastewater. Coagulation was carried out with rapid stirring at 100 rpm for 1 minute. Then flocculated using 1% basefloc polyelectrolyte 3 mL each. Flocculation with slow stirring at 25 rpm for 15 minutes. The results of the jar test were measured for turbidity, pH, and the type of floc. The results showed that the optimum dose of PAC coagulant to treat leather tanning waste was 5 mL PAC 2% for a waste volume of 300 mL, at pH 7. This result can be converted into grams of PAC/waste volume, namely 0.1 grams of PAC/300 mL of waste or 0.33 grams of PAC/1L of leather tanning liquid waste.